Association between Low Density Lipoprotein Receptor-Related Protein 2 Gene Polymorphisms and Bone Mineral Density Variation in Chinese Population - Wang, Chun (Public Library of Science, 2011)
Low density lipoprotein receptor-related protein 2 gene (LRP2) is located next to the genomic region showing suggestive linkage with both hip and wrist bone mineral density (BMD) phenotypes. LRP2 knockout mice showed severe vitamin D deficiency and bone disease, indicating the involvement of LRP2 in the preservation of vitamin D metabolites and delivery of the precursor to the kidney for the generation of 1α,25(OH)(2)D(3). In order to investigate the contribution of LRP2 gene polymorphisms to the variation of BMD in Chinese population, a total of 330 Chinese female-offspring nuclear families with 1088 individuals and 400 Chinese male-offspring nuclear families with 1215 individuals were genotyped at six tagSNPs of the LRP2 gene (rs2389557, rs2544381, rs7600336, rs10210408, rs2075252 and rs4667591). BMD values at the lumbar spine 1–4 (L1-4) and hip sites were measured by DXA. The association between LRP2 polymorphisms and BMD phenotypes was assessed by quantitative transmission disequilibrium tests (QTDTs) in female- and male-offspring nuclear families separately. In the female-offspring nuclear families, rs2075252 and haplotype GA of rs4667591 and rs2075252 were identified in the nominally significant total association with peak BMD at L1-4; however, no significant within-family association was found between peak BMD at the L1-4 and hip sites and six tagSNPs or haplotypes. In male-offspring nuclear families, neither the six tagSNPs nor the haplotypes was in total association or within-family association with the peak BMD variation at the L1-4 and hip sites by QTDT analysis. Our findings suggested that the polymorphisms of LRP2 gene is not a major factor that contributes to the peak BMD variation in Chinese population.